DEVELOPMENT AND EVALUATION OF QUICK COOKING REDGRAM DHAL (CAJANUS CAJAN L.) - M. BHAGYAMMA; V. SANDHYA RANI, APARNA KUNA, M. SREEDHAR, CH. JAGAN, D. SHARANYA RANI (The Journal of Research, PJTSAU, 2020)
Four different treatments (T1 and T2 treatments included soaking in 1% hot and cold NaCl solutions;T3 and T4 treatments included soaking, autoclaving, cooling, freezing and dehydrating redgram dhal) were standardized for development of quick cooking dhal. Protein, ash, carbohydrate and energy content were highest in T3 and T4 treatments. Cooking time was lowest in T3 (7 minutes) followed by T4 (6 minutes) treatments as compared to T1, T2 and control samples. Water absorption was also highest in T3 and T4 treatments indicating good volume expansion of dhal. Solids dispersed were lower in T3 and T4 treatments as compared to control red gram dhal. The colour values of T3 and T4 quick cooking dhal treatments were also at par with the control samples indicating good visual appeal of the dhal.